2018
DOI: 10.1038/s41467-018-06560-z
|View full text |Cite
|
Sign up to set email alerts
|

Cortical population activity within a preserved neural manifold underlies multiple motor behaviors

Abstract: Populations of cortical neurons flexibly perform different functions; for the primary motor cortex (M1) this means a rich repertoire of motor behaviors. We investigate the flexibility of M1 movement control by analyzing neural population activity during a variety of skilled wrist and reach-to-grasp tasks. We compare across tasks the neural modes that capture dominant neural covariance patterns during each task. While each task requires different patterns of muscle and single unit activity, we find unexpected s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
254
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(300 citation statements)
references
References 72 publications
18
254
3
Order By: Relevance
“…Our findings are in line with previous work showing that activity in a large population of neurons is confined to a lower dimensional manifold [Mante et al, 2013, Chaisangmongkon et al, 2017, Remington et al, 2018, Gallego et al, 2018. We found striatal and prefrontal responses encoded the sequence task on a low-dimensional manifold.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with previous work showing that activity in a large population of neurons is confined to a lower dimensional manifold [Mante et al, 2013, Chaisangmongkon et al, 2017, Remington et al, 2018, Gallego et al, 2018. We found striatal and prefrontal responses encoded the sequence task on a low-dimensional manifold.…”
Section: Discussionsupporting
confidence: 93%
“…We determined the muscle synergies with PCA as we were interested in analyzing the computational implications of motor modularity without regard to the actual physiological implementation (e.g., in the spinal circuitry [15] or in cortex [21]), which is unknown. We observed a decrease in performance when performing the experiments with NNMF, using the solver provided in Kim et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we examined the relationship between the texture and speed representations by assessing the extent to which changes in one interfered with the other. To this end, we computed the proportion of speed-related variance that was captured by each dimension of the texture representation ( Figure 2C), a quantity we refer to as the alignment index (Elsayed et al, 2016;Gallego et al, 2018)(see Methods). We found that speed-driven changes were primarily captured by the first principal component of the texture representation and this relationship was far stronger in the periphery than in cortex (average alignment index, peripheral: 0.80, cortical: 0.46).…”
Section: Population Representations Of Texture and Speedmentioning
confidence: 99%
“…To determine the amount of overlap between the texture space and the speed dimension, we calculated an alignment index (Elsayed et al, 2016;Gallego et al, 2018), which we defined as the amount of speeddriven variance captured by the texture space, normalized by the total amount of speed-related variance in the population response. Specifically, we define the alignment index as:…”
Section: Neural Population Analysesmentioning
confidence: 99%